Core Values, Challenges, and Cultural Change: 50+ Years of Outward Bound New Zealand Courses. (September 2020) - Martin, Andrew; Mott, Melanie; Watson, Geoff
Background: Outward Bound New Zealand (OBNZ) was established in 1962, as part of an international network of outdoor education schools founded in the United Kingdom by Kurt Hahn, with the central values of empowering people to fulfill their potential, fostering compassion, and developing courage.Purpose: The purpose of this study was to provide an empirical case study of an organization evolving according to an industry life cycle, by examining OBNZ's changing values and how they have maintained their Classic 21-day courses.Methodology/Approach: The research involved semi-structured, in-depth interviews with past School and Executive Directors ( n = 14).Findings/Conclusions: During the 1990s, OBNZ encountered major challenges, which required significant organizational change, but their core business is still the classic course. OBNZ's values have been repeatedly reviewed but remain aligned to its fundamental vision: better people, better communities, better world .Implications: Hahn's value of compassion has remained central to OBNZ; however, the Māori [indigenous people of New Zealand] concept of kaitiakitanga [guardianship] has also been integrated into its philosophy. Maintaining its core values has sustained this progressive value-based organization over the past 50+ years.